Ensino de leitura e escrita para aprendizes com deficiência intelectual - Santos, Sonia Cristina Esplendor dos (2012)
The repertoires of reading and writing are fundamental to improve the quality of life of all people. These repertoires are rarely taught to people with intellectual disabilities. There is a great distrust by the part of society in the learning abilities of people with intellectual disabilities and also among teachers there is a disbelief about effective teaching procedures, which allow acquiring repertoires complexes, like reading and writing. Behavior Analysis offers contributions from stimulus equivalence model. The literature indicates that teaching conditional relations between sound and visual stimuli (pictures and text), reading and writing can be installed and developed. The aim of this study was to apply a teaching procedure for the acquisition of reading and writing for learners with intellectual disabilities, using educational software Mestre ®. Participants were four individuals with intellectual disabilities, aged between 15 and 21 years. The study was organized into five steps and the stimuli used were dictated words (A), pictures (B) and written words (C). The relations AB, CC, BC, CE and AE were taught and the relations AC, CB were tested, and also reading (CD relation) and writing (BE relation). The generalization tests included reading and writing handwritten words and phrases. Considering the time of training (maximum of 8 hours), and comparing the performance of participants before and after training, it can be stated that the teaching procedure had a positive effect, because there was significant change in the repertoires of the participants' reading and writing. The results were discussed aspects of the teaching procedure and suggestions were made for further investigations